MGP T-138C Polymorphism (TT Genotype) is Associated with Vascular Calcification Incidence in Indonesian Regular Hemodialysis Patients - Muhammad Hanif Wibowo; Riri Andri Muzasti; Syafrizal Nasution (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Vascular calcification contributes greatly to the incidence of cardiovascular disease. Previously, vascular calcification was considered as a passive process caused by the mineral deposition from the circulation. Nowadays, researchers have found inhibitors and promoter factors from vascular calcification, one of which is the matrix gla protein (MGP). MGP levels depend on the gene that encodes them. The MGP T-138C polymorphism is one of the most common causes of vascular calcification.METHODS: This was a case-control study involving 86 chronic kidney disease (CKD) patients who underwent regular hemodialysis in Rasyida Kidney Hospital, Medan, Indonesia. Vascular calcification was determined from lateral and posteroanterior abdominal X-ray. The MGP T-138 C polymorphism was analyzed using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP).RESULTS: The TT/TC genotype associates with the incidence of vascular calcification with OR of 3.52, 95% CI: 1.23-10.106 (p-value<0.001).CONCLUSION: There is an association between MGP T-138C polymorphism, particularly on T Allele with the incidence of vascular calcification in CKD patients undergoing regular hemodialysis.KEYWORDS: hemodialysis, T-138 C polymorphism, vascular calcification, matrix GLA protein